Costanza di Svevia, Regina d'Aragona in Sicilia - Rotolo, Filippo (Miscellanea francescana, 2023)
Fr. Filippo Rotolo OFMConv of the Province of Sicily, a well-known author on Franciscan matters, former collaborator of our Miscellanea Francescana, now in the peace of God († 2014), deals with Constance, queen of Aragon and Sicily in twelve brief paragraphs and presents the religious aspect, an almost unpublished theme, in the history studies of the Kingdom of Aragon in Sicily. She was born around 1249-1250 in Catania from Manfredi, the illegitimate son of emperor Frederick II of Swabia and Beatrice of Savoy, in 1267. She became the twelve-year-old bride of the king of Aragon Peter III. In Aragon, where this wellmatched royal couple fathered six children (one of whom, Elizabeth of Portugal, was canonised a saint), Constance remained until 1282 when, following the War of the Vespers, Peter III asserted the right of his wife to the kingdom of Sicily, taken by force from the Angevins for their corruption. The article follows the various stages of queen Constance in Sicily, an itinerary that was anything but happy, she a fervent Catholic, marred by the excommunications of the popes, feudal lords of Sicily, by the early death of her husband and some children and, above all, by the fratricidal struggle of the children, Federico III, king of Sicily, and Giacomo II, king of Aragon, who joined the Angevins. Very devoted to St. Francis and the Franciscans, like all her royal family, and despite not having taken religious vows, she often wore the habit of St. Clare as a sign of penance. Absolved from the excommunication, she died on April 8th, 1300, in Barcelona, and attired in the Poor Clare habit, she was buried in the church of St. Francis alongside her husband and two of her children, who were also attired in the Franciscan habit.